Evaluation of a translational swine model of respiratory hypersensitivity induced by exposure to Phleum pratense pollen allergens - Ledesma-Aparicio, Jessica; Salazar-Guerrero, Gustavo; Soto-Muñoz, Axel; Ramírez-Estudillo, Carmen; Gómez-Esquivel, Mónica Luz; Reyes-Grajeda, Juan Pablo; Reyes-López, César A.; Vega-López, Marco A. (Frontiers in Allergy, 2025)
IntroductionAsthma is a disease characterized by chronic inflammation of the airway mucosa that causes tissue remodeling and a reversible decrease in airflow. The causative agent of asthma is still unknown; however, several studies have shown that environmental factors such as allergens present in pollens are involved. This project's objective was to develop and evaluate a model of respiratory hypersensitivity in Vietnamese minipigs, which is closer in many aspects to humans than rodents, using Phleum pratense allergenic pollen extract.MethodsIn this hypersensitivity model, human-like signs were observed during a challenge with the allergens. Intradermal and passive anaphylaxis tests confirmed that specific IgE mediated the response.ResultsSignificant changes in lung tissue remodeling, high levels of serum allergen-specific IgA, IgG, and to a lesser extent IgE were found in the sensitized pigs, which could favor tolerance and pathogenesis. However, since chronic pathology did not develop, elevated levels of cytokines were not proven.DiscussionThis work demonstrated that the immunization protocol in this experimental model can induce a type I respiratory hypersensitivity-like response mediated by antigen-specific IgE, with pathophysiological similarities to those of humans and prospective for translational basic and applied research.